Efeitos da gramínea invasora Urochloa Decumbens Stapf (Poaceae) sobre a seleção do habitat de nidificação do Atobá-pardo (Sula Leucogaster, 1783) na Ilha do Castilho, Brasil - Almeida, Gabriela Godinho de (Universidade Federal de São Carlos, 2017)
Biological invasion is listed among the major threats to native biodiversity, causing several impacts. In cases of invasion by exotic plants, vegetation composition and structure are usually changed. These characteristics influence directly on nesting habitat selection by birds at different spatial scales, and may affect their distribution and reproductive success. In this study, we investigated the interference of Urochloa decumbens Stapf., an aggressive invasive grass and which has a rapid proliferation, on nest-habitat selection by the brown-booby (Sula leucogaster Boddaert, 1783) in a Brazilian oceanic island, Castilho Island. At macroscale, the use of available invaded areas and native vegetation areas for nesting were compared. For microscale, different vegetation parameters were estimated 1 m around the nests in plots within invaded and native areas. The difference on the number of nests and vegetation parameters between invaded and native plots was tested. Lastly, the relationship between the number of nests per plot and vegetation parameters was evaluated through the construction of mixed-models. It was found rejection of invaded areas for nesting and preference for areas of native vegetation at macroscale. Plots in invaded areas had a significant lower number of nests, lower coverage proportion by native grasses and herbaceous cover, higher coverage proportion by U. decumbens and higher height of vegetation than native plots. At the microscale, the coverage proportion by invasive grass was the main variable affecting the choice, being negatively associated to the nest-site. Results indicate the importance of controlling U. decumbens to ensure the availability of appropriate nesting habitats for this seabird species.
Keywords: Plantas invasoras; Seleção de habitat; Local do ninho; Reprodução; Aves marinhas; Alien plants; Habitat selection; Nest-site; Reproduction; Seabirds; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS